Drivers of Adverse 30-Day Quality Outcomes after Microvascular Decompression for Trigeminal Neuralgia Analysis from a National Surgical Quality Registry. (16th November 2020) - Alvi, Mohammed A; Doherty, Ronan; Kerezoudis, Panagiotis; Yolcu, Yagiz U; Agarwal, Vijay; Ghogawala, Zoher
Abstract: INTRODUCTION: Microvascular decompression (MVD) is an effective neurosurgical intervention for trigeminal neuralgia in patients whose pain is refractory to medical therapy. Suboccipital approach (SOA) is the most commonly utilized approach for MVD; however a subtemporal approach (STA) may also be used. METHODS: The National Surgical Quality Improvement Program (NSQIP) database was used to identify patients with trigeminal neuralgia (ICD-9 335.1; ICD-10 G50.0) having undergone a suboccipital MVD (CPT = 61458, 61460, 61343, 61480) or subtemporal MVD (CPT = 61450, 61595, 61590) between 2005–2018 RESULTS: We identified 1, 015 patients, of which 892 (87.9%) underwent a suboccipital approach (SOA) and 123 (12.1%) underwent a subtemporal approach (STA). STA was associated with a higher rate of 30-day readmission (12.2%, n = 15 vs 6.1%, n = 54, P = .011) On multivariable-analysis, adjusting for patient related and clinical factors, STA was associated with higher odds of 30-day readmission (OR 2.27; 95%CI 1.22-4.21; P = .009). The most common reasons for 30-day readmission overall and for both groups were found to be CSF leak (23.2% of all readmissions, n = 16) and surgical site infection (20.3% of all readmissions, n = 14). Other factors associated with higher readmissions included male sex (OR 1.78; 95%CI 1.06-3.01; P = .029), American Soceity of Anaesthesiology (ASA) grade 3/4 (OR 1.85; 95%CI 1.06-3.25; P = .031) and diabetes (OR 2.66; 95%CI 1.26-5.62; P = .01). For prolonged length of stay, significant factors included an ASA grade 3/4 (OR 1.68; 95%CI 1.19-2.36; P = .003); for non-routine discharge, significant factor included age over 65 (OR 3.38; 95%CI 1.16-9.82; P = .025); and for reoperation rate, significant factors included increased BMI (OR 1.80; 95%CI 1.19-2.71; P = .005), and diabetes (OR 2.89; 95%CI 1.10-7.60; P = .031). CONCLUSION: Our analyses indicate that subtemporal approach, obesity, diabetes and higher ASA grade may be associated with adverse 30-day outcomes among patients undergoing MVD for trigeminal neuralgia.